Determination of optimal alkaline treatment conditions for fique fiber bundles as reinforcement of composites materials - Castro, Cristina; Palencia, Ana; Gutiérrez, Iván; Vargas, Gustavo; Gañán, Piedad (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
For the last decades, natural fibers have been used as reinforcement of friendly environmental polymeric composites, due to their technical, economical and environmental advantages that include: moderate mechanical and thermal properties. How ever, the OH groups in some of their chemical structures like cellulose, reduce the compatibility with hydrophobic polymeric matrices such as polyolefines. Natural fiber, usually are exposed to chemical and physical treatment to reduce their hydrophilic tendency and to enhance fiber/matrix adhesion. Alkalinization, alkali treatment or mercerization, is one of the most common procedures applied on natural fibers. This process introduces important changes on its mechanical properties, physical and morphological characteristics, and chemical composition. In spite of other studies, it is necessary de fine surface treatment conditions in accordance with industrial processing and environmental considerations. In this study, the influence of different alkali treatment conditions on the fique fiber tensile behavior has been evaluated. Treatment parameters as solution concentration, exposure time and dry conditions have been analyzed. Fourier transformation infrared spectrophotometry (FTIR) analysis, atomic force (AFM) and optical microscopies have been used to evaluate alteration on chemical and morphological characteristics. Treatment conditions that include low solution concentration bring a good enough quality in the mechanical behavior required by fique fiber bundles as polymeric reinforcement.